Stimulating motor competence through field games: an experimental study on elementary school students - Gustian, Uray; Samodra, Y. Touvan Juni; Gandasari, Fatima Maharani; Yosika, Ghana Fiesta (Jurnal Keolahragaan, 2023)
Motoric competence is a competency that requires understanding in carrying out physical activities. However, in the learning process motor competence is carried out without the support of understanding so that it results in students experiencing difficulties and confusion in executing the motor skills they have when in a different environment during training or learning. The research aims to measure the success of stimulation of motor competence by using the field games approach. The research was conducted in the pre-experimental type with the One Group Pretest Posttest Designs type. The experiment was conducted on twelve elementary school students in fourteen meetings. The research involved twelve fourth grade elementary school students who were taken randomly by selecting numbers at random. The instrument for measuring students' motor skills used the Test of Gross Motor Development revision 2 edition (TGMD-2) and understanding of playing using the Games Performance Assessment Instrument (GPAI) and the measurement results were analyzed using a quantitative descriptive method. The results showed that there had been an increase in the rating of students' motor skills and the average score of students' games performance. This result is due to the learning that is carried out using the field games approach which is able to encourage students to be active in making movements and facilitating metacognition processes such as decision making, critical thinking, and problem-solving. The conclusion of learning done with the field games approach can stimulate students' motor competence